Wnt Signaling Cascade in Dendritic Cells and Regulation of Anti-tumor Immunity - Suryawanshi, Amol; Hussein, Mohamed S.; Prasad, Puttur D.; Manicassamy, Santhakumar (Frontiers in Immunology, 2020)
Dendritic cells (DCs) control the strength and quality of antigen-specific adaptive immune responses. This is critical for launching robust immunity against invading pathogens while maintaining a state of tolerance to self-antigen. However, this also represents a fundamental barrier to anti-tumor immune responses and cancer immunotherapy. DCs in the tumor microenvironment (TME) play a key role in this process. The factors in the TME and signaling networks that program DCs to a regulatory state are not fully understood. Recent advances point to novel mechanisms by which the canonical Wnt signaling cascade in DCs regulates immune suppression and the same pathway in tumors is associated with the evasion of antitumor immunity. Here, we review these recent advances, in the context of the pleiotropic effects of the Wnts in shaping anti-tumor immune responses by modulating DC functions. In addition, we will discuss how Wnt/β-catenin pathway in DCs can be targeted for successful cancer immunotherapy.